Learning about Schools in the British Isles Through a Video Corpus: Reflections on an Online Project for Digital Literacy and Multimodal Corpus Construction - Cambria, Mariavita (Revija za elementarno izobraževanje, 2023)
Through first-hand experiences undertaken with students using the OpenMWS platform (Taibi 2020), the paper reports on the progress made by second-year language degree students in English linguistics at the University of Messina as regards their use of online corpus construction, annotation and search tools when exploring video genres. The paper describes the ways in which participation in the Messina OVP (Online Video Project) on schools in the British Isles during and after the Covid crisis has proved beneficial for the students in question, both in terms of acquiring textual competences and as regards creating new interactive communities (Vasta and Baldry 2020; Baldry et al 2022).
Keywords: Multimodality, corpus construction and annotation, digital literacy, English linguistics, video genres.